2021
DOI: 10.7759/cureus.12521
|View full text |Cite
|
Sign up to set email alerts
|

The Iris Thickness in a Healthy Saudi Population

Abstract: Purpose Iris thickness (IT), a known risk factor for angle closure glaucoma, has not been evaluated in the normal Saudi population. Methods Quantitative information on IT was evaluated in healthy Saudi eyes using anterior segment optical coherence tomography (ASOCT). IT and iris volume was measured with the room ‘light on’ (LON) and ‘light off’ (LOFF) using Image J software. IT in the nasal and temporal iris was measured at 500 µm (IT500) and 750 µm (IT750) from the scleral spu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…However, studies from Denmark and Japan reported greater choroidal volume in males compared with females [11,20]. Interestingly, in healthy Saudi adults, the iris is thicker in males than in females [13].…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…However, studies from Denmark and Japan reported greater choroidal volume in males compared with females [11,20]. Interestingly, in healthy Saudi adults, the iris is thicker in males than in females [13].…”
Section: Discussionmentioning
confidence: 91%
“…However, studies from Denmark and Japan reported greater choroidal volume in males compared with females [ 11 , 20 ]. Interestingly, in healthy Saudi adults, the iris is thicker in males than in females [ 13 ]. Differences in CT by sex in the Arab race in our study and studies on Asian and European populations need further confirmation with a larger sample size.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Normal data (biometrics) about the anterior component of the eye globe including anterior segment depth, ACA, iris thickness, and ciliary body thickness are needed before deciding if this eye is normal or abnormal, and these data are missing in the literature [ 31 ]. These structures can be evaluated by either UBM or anterior segment OCT [ 32 , 33 ], and differences may exist between different populations [ 34 , 35 , 36 ], and may exist with special ocular diseases including intraocular tumors, glaucoma, myopia, and retinal detachment [ 37 , 38 , 39 , 40 ].…”
Section: Discussionmentioning
confidence: 99%